Involving students in a collaborative and reflective reading material development: A participatory action research study: participatory action research - Nimasari, Elok Putri; Harmanto, Bambang; Bonavidi, Rinjani; Cobantoro, Adi Fajaryanto; Elvina Dwi, Cahyani; Velrinda Fahza'a, Risty (JEES (Journal of English Educators Society), 2025)
Grounded in Halliday’s Systemic Functional Linguistics and Freire’s Critical Pedagogy, this participatory action research aims to develop a transformative digital reading assessment model that embeds cultural values and promotes critical literacy. Conducted over four months at an Islamic-Muhammadiyah higher education institution in Indonesia, this study involved 30 student participants and several community figures. Data were collected through classroom observations, focus group discussions, and interviews, and analyzed using critical discourse analysis informed by SFL's meta functions and Freirean principles. Findings reveal three key themes: (1) students interpreted texts as ideological constructs by identifying field, tenor, and mode; (2) students co-constructed culturally situated reading materials through dialogic engagement with community members; and (3), students critically engaged with multimodal digital texts by analyzing how visual and linguistic elements shaped meaning. This study offers a practically grounded model for reading assessment, showing how digital platforms can serve as ethical spaces for language learning that is both critical and culturally embedded.